2022
DOI: 10.3389/fncom.2022.902741
|View full text |Cite
|
Sign up to set email alerts
|

Ramping activity in the striatum

Abstract: Control of the timing of behavior is thought to require the basal ganglia (BG) and BG pathologies impair performance in timing tasks. Temporal interval discrimination depends on the ramping activity of medium spiny neurons (MSN) in the main BG input structure, the striatum, but the underlying mechanisms driving this activity are unclear. Here, we combine an MSN dynamical network model with an action selection system applied to an interval discrimination task. We find that when network parameters are appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 131 publications
(207 reference statements)
0
1
0
Order By: Relevance
“…Here we take steps, using computational modeling, to try to understand how aberrant striatal cell assembly population dynamics relates to the complex array of underlying cellular and synaptic pathophysiologies found in PD and LID. In previous work (Ponzi and Wickens, 2008 , 2010 , 2012 , 2013 , 2022 ; Ponzi et al, 2020 ) we showed that an inhibitory MSN network could generate switching cell assembly activation patterns in good agreement with experimental studies (Carrillo-Reid et al, 2008 ), providing network parameters, in particular the strength and distribution of excitatory driving and the strength of recurrent inhibition between MSNs, was appropriate for the striatum. However when network parameters are altered away from their true striatal values, various types of pathological cell assembly dynamics can be found (Ponzi and Wickens, 2012 , 2022 ; Ponzi et al, 2020 ) including patterns resembling those found in 6OHDA and LID slices.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Here we take steps, using computational modeling, to try to understand how aberrant striatal cell assembly population dynamics relates to the complex array of underlying cellular and synaptic pathophysiologies found in PD and LID. In previous work (Ponzi and Wickens, 2008 , 2010 , 2012 , 2013 , 2022 ; Ponzi et al, 2020 ) we showed that an inhibitory MSN network could generate switching cell assembly activation patterns in good agreement with experimental studies (Carrillo-Reid et al, 2008 ), providing network parameters, in particular the strength and distribution of excitatory driving and the strength of recurrent inhibition between MSNs, was appropriate for the striatum. However when network parameters are altered away from their true striatal values, various types of pathological cell assembly dynamics can be found (Ponzi and Wickens, 2012 , 2022 ; Ponzi et al, 2020 ) including patterns resembling those found in 6OHDA and LID slices.…”
Section: Introductionsupporting
confidence: 83%
“…In previous work (Ponzi and Wickens, 2008 , 2010 , 2012 , 2013 , 2022 ; Ponzi et al, 2020 ) we showed that an inhibitory MSN network could generate switching cell assembly activation patterns in good agreement with experimental studies (Carrillo-Reid et al, 2008 ), providing network parameters, in particular the strength and distribution of excitatory driving and the strength of recurrent inhibition between MSNs, was appropriate for the striatum. However when network parameters are altered away from their true striatal values, various types of pathological cell assembly dynamics can be found (Ponzi and Wickens, 2012 , 2022 ; Ponzi et al, 2020 ) including patterns resembling those found in 6OHDA and LID slices. Here we quantitatively estimate computational network model parameters from empirical slice data using the deep learning framework, Simulation Based Inference (SBI).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Medium spiny neurons (MSNs) are the principal neurons in the striatum. These neurons express both adenosine and dopamine receptors, and they are a key component of the basal ganglia and play a crucial role in regulating timing processes [39,40]. MSNs receive inputs from various cortical regions, including the prefrontal cortex (PFC), motor cortex, and sensory cortices.…”
Section: Plos Onementioning
confidence: 99%